Cyber security applications for industry 4.0 - Sujatha, R.; Prakash, G.; Jhanjhi, Noor Zaman, 1972- (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Cyber Security Applications for Industry 4.0 (CSAI 4.0) provides integrated features of various disciplines in Computer Science, Mechanical, Electrical, and Electronics Engineering which are defined to be Smart systems. It is eminent that Cyber-Physical Systems (CPS) provide accurate, real-time monitoring and control for smart applications and services. With better access to information from real-time manufacturing systems in industrial sectors, the Cyber-Physical Systems aims to increase the overall equipment effectiveness, reduce costs, and improve efficiency. Industry 4.0 technologies are already enabling numerous applications in a variety of industries. Nonetheless, legacy systems and inherent vulnerabilities in an organization's technology, including limited security mechanisms and logs, make the move to smart systems particularly challenging"--
OCLC-licensed vendor bibliographic record.
Keywords: Industry 4.0 -- Security measures; Computer networks -- Security measures; COMPUTERS / Internet / Security